Research of smoothness on torque coordination of two-wheel independently driven hub electric vehicle based on fuzzy control. (July 2019) - Zhang, Chuanwei; Zhang, Dongsheng; Zeng, Hongjun; Wang, Rui; Wen, Jianping; Mo, Wei
Aiming at the problems of drive torque coordination, steering vibration and asymmetry of two-wheel independent drive hub electric vehicle, a new torque coordination control algorithm of driving wheel is proposed based on fuzzy control theory. The algorithm takes yaw rate deviation and centroid side deviation as inputs of fuzzy controller, outputs additional yaw moment needed by vehicle, and distributes it to each driving wheel reasonably according to the requirements of each driving wheel. Under the coordination of the driving anti-skid control algorithm, the vibration of driving wheels was reduced and the vehicle can run smoothly. The algorithm is verified by Simulink-CarSim joint simulation, and a fast prototype experiment platform based on dSPACE is built. The results of experiment and simulation show that the control strategies are effective and feasible.